Effects of monoclonal antibodies to the alpha and beta chains of the human lymphocyte function-associated (H-LFA-1) antigen on T lymphocyte functions. - Dongworth, D; Gotch, F; Hildreth, J; Morris, A; Mcmichael, A (1985)
The ability of two antibodies, one specific for the alpha chain, p180, and the other for the beta chain, p95, of the human lymphocyte function-associated (LFA-1) antigens, to inhibit T cell function was measured. Both antibodies inhibited T cell-mediated lysis of virus-infected target cells and of K562 cells. Only the anti-beta chain antibody inhibited natural killer cell lysis of K562. The antibodies inhibited cytotoxic T lymphocyte cell (CTL) lysis of HLA-mismatched target cells in the presence of concanavalin A at 6.25-12.5 micrograms/ml, but at higher doses of Con A no inhibition was seen. When the lytic process was divided into calcium-independent (adherence) and -dependent (lysis) steps the antibodies were found to block at the initial step of conjugate formation. The effects of these antibodies on T cell proliferative responses showed that responses to antigens, alloantigens, mitogens and anti-CD3 (UCHT1) antibody were greatly inhibited. All of these responses are adherent cell dependent and proliferation of adherent cell-depleted mononuclear cells to Sepharose-coupled UCHT1 was not inhibited by anti-LFA-1 antibodies. Proliferation to paired anti-CD2 (T11) antibodies was also only weakly inhibited. Release of interferon-gamma by CTL on contact with target cells was also inhibited by anti-LFA antibody. These results are evidence that the LFA antigen is necessary for a nonspecific interaction with antigen-presenting cells that is essential for activation of T cells through the CD3-T cell receptor complex.